Kesiapan Angkutan Jalan Dalam Menghadapi Penerapan Standar Emisi Euro 4 - Maulidya, Ichda (Warta Penelitian Perhubungan, 2019)
The Readiness of Road Transportation in Facing the Implementation of Standard Implementation for Euro 4 Emissions: The consumption of fuel oil is quite influenced by the increase in the number of motorized vehicles every year. The consumption also tends to increase with an average growth of 4.24% per year. If left uncontrolled, this is then supposed to trigger an increase in greenhouse gas (GHG) emissions. Thus, as an effort to reduce the impact of greenhouse gas emissions, the Government of Indonesia will immediately impose Euro 4 emission standards for new types of motor vehicles and those being produced gradually by which gasoline-fueled vehicles in October 2018 and vehicles diesel fuel (diesel) in March 2021. The advantages of implementing the Euro 4 Emission Standard compared to the previous standard (Euro 2) are being able to reduce emissions significantly, save fuel subsidies, and increase the competitiveness of automotive production and market share in the international level. In this research, the priority strategies that need to be carried out by stakeholders in the implementation of Euro 4 Emission Standards for road transport will be analyzed. The research method used SWOT two factors, including internal and external to determine priority strategies. Internal factors include strengths and weaknesses, while external factors deal with the opportunities and threats. According to the results of the research, it is known that the obtained priority strategy was the strategy that used strength (Strengths/S) to take advantage of opportunities (O) including the need to gradually implement greenhouse gas mitigation regulations, especially for the automotive industry in order to encourage increased exports of motor vehicles, develop the technology dealing with the test of motor vehicles types which have the standard of Emisi Euro 4 in Indonesa to increase either the domestic production or exports target, take an advantage of the market to boost the export of motor vehicles, and improve the quality of fuel oil (BBM) in Indonesia in Euro 4 Emission to maintain the performance of motor vehicles either for dometic or for export purposes.Keywords: Motorized vehicles, emission, greenhouse gases and Euro 4. Konsumsi bahan bakar minyak cukup dipengaruhi oleh peningkatan jumlah kendaraan bermotor setiap tahunnya. Konsumsi tersebut juga cenderung mengalami peningkatan dengan rata-rata pertumbuhan sebesar 4,24% per tahun. Jika dibiarkan, maka hal ini disinyalir akan memicu peningkatan emisi Gas Rumah Kaca (GRK). Oleh karena itu, sebagai salah satu upaya pengurangan dampak emisi GRK, Pemerintah Indonesia akan segera memberlakukan standar emisi Euro 4 untuk kendaraan bermotor tipe baru maupun yang sedang diproduksi secara bertahap yaitu pada Oktober 2018 untuk kendaraan berbahan bakar bensin dan pada Maret 2021 untuk kendaraan berbahan bakar diesel (solar). Keunggulan penerapan Standar Emisi Euro 4 dibandingkan dengan standar sebelumnya (Euro 2) yakni mampu menurunkan emisi secara signifikan, menghemat subsidi bahan bakar, serta meningkatkan daya saing produksi otomotif serta pangsa pasar di kancah internasional. Penelitian ini akan menganalisis strategi prioritas yang perlu dilakukan para stakeholder dalam penerapan Standar Emisi Euro 4 bagi angkutan jalan. Metode penelitian yang digunakan adalah analisis SWOT dengan  menggunakan dua faktor, meliputi internal dan eksternal untuk menentukan strategi prioritas. Faktor internal mencakup kekuatan dan kelemahan, sedangkan faktor eksternal mencakup peluang dan ancaman. Berdasarkan hasil penelitian, diketahui bahwa strategi prioritas yang digunakan merupakan strategi dengan memanfaatkan kekuatan (Strengths/S) untuk mengambil manfaat dari peluang (opportunities/O) yang meliputi perlunya implementasi regulasi mitigasi GRK secara bertahap khususnya untuk industri otomotif guna mendorong peningkatan ekspor kendaraan bermotor, mengembangkan teknologi uji tipe kendaraan bermotor berstandar Emisi Euro 4 di Indonesia agar target produksi domestik maupun ekspor meningkat, memanfaatkan pangsa pasar untuk mendongkrak ekspor kendaraan bermotor, serta meningkatkan kualitas Bahan Bakar Minyak (BBM) di Indonesia yang berstandar Emisi Euro 4 agar performa mesin kendaraan bermotor terjaga, baik untuk keperluan domestik maupun ekspor.Kata kunci : Kendaraan bermotor, emisi, gas rumah kaca dan Euro 4.